Confronting controversial issues in History classrooms: An analysis of preservice High School teachers’ experiences in post-apartheid South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The purpose of the study presented in this article is to understand the experiences of final year pre-service South African high school history teachers on their engagement with controversial issues during their teaching practice. The rationale for undertaking this study was twofold: filling a gap in the existing literature, which has neglected the experiences of pre-service teachers and their understandings of controversial issues in history during the early stages of their professional development, and for us to learn from our students so as to possibly contribute to a more meaningful school history education in present-day South Africa. The data for this study was drawn from a collection of reflective reports prepared by 75 preservice high school history teachers on their experiences of teaching controversial issues during their professional practice sessions. We found that the student-teachers’ experiences in this regard greatly varied, and were informed by multifarious factors, including the pre-service teachers’ positionality, the institutional culture of their placement schools, their professional relationships with the mentor teachers, and their engagement with learners, policy documents and teaching material. What stood out was the centrality of race to their experiences of teaching controversial issues, something which revealed the deep-rooted legacies of South Africa’s racist past. The consequence of this was a black/white binary that continued to influence the way certain schools, pre-service teachers, mentor teachers and learners relate to history and to each other.
Keywords: Controversial issues; Pre-service history teachers; Post-apartheid; History classrooms; Student- and mentor teacher’s relationships